End-user encounters with lambda abstraction in spreadsheets: Apollo's bow or Achilles' heel? - Sarkar, Advait; Ragavan, Sruti Srinivasa; Williams, Jack; Gordon, Andy (IEEE Symposium on Visual Languages and Human-Centric Computing (VL/HCC), 2022)
The value of computational abstractions to non-expert end-user programmers is contentious. We study reactions to the LAMBDA function in Microsoft Excel, which enables users to define their own functions using the spreadsheet formula language, through a thematic analysis of nearly 2,700 comments posted on the Reddit, Hacker News, YouTube, and Microsoft Tech Community online forums. We find that computational abstractions are viewed both as helpful and harmful, that users encounter learning and understanding barriers to applying them, and that there are deficiencies and opportunities in tooling such as in formula editing, versioning, reuse and sharing. We find that the introduction of LAMBDA prompts new debate around whether spreadsheets are code, whether writing formulas can be considered programming, and whether spreadsheet users identify themselves as programmers.